The Determination of Shortest Path Using Genetics Algorithm Assisted Matlab - Hendra Cipta; Rina Widyasari (IJISTECH (International Journal of Information System and Technology), 2020)
The problem is taking the shortest path for a road driver is an interesting thing. This paper explains how to find the shortest path using a genetic algorithm to achieve the best solution. Then it shows how to implement the genetic algorithm using the MATLAB program. For example, it is given a connected directed graph containing 20 vertices and 41 arcs where these vertices are assumed to be cities.